Effect of different levels of skin disruption and contact with oxygen during grape processing on phenols, volatile aromas, and sensory characteristics of white wine. Issue 7 (25th April 2019) - Lukić, Igor; Horvat, Ivana; Radeka, Sanja; Damijanić, Kristijan; Staver, Mario
Abstract: To investigate the changes in wine chemical composition, sensory quality, and style induced by various levels of skin disruption and contact with oxygen during grape processing, five treatments were applied: whole grape cluster pressing in semi‐reductive conditions (WCP‐R), whole grape cluster pressing in standard conditions (WCP), standard grape mash pressing as a control (GMP), light (LOX), and heavy oxidation of grape juice (HOX). Produced wines were subjected to analysis of phenols (HPLC‐DAD) and volatiles (HS‐SPME‐GC/MS), as well as quantitative descriptive sensory analysis. WCP‐R wines stood out with the highest amounts of hydroxycinnamates and preserved aromas, and the highest intensities of positive sensory attributes. Both WCP and LOX treatments significantly reduced phenols when compared to GMP, while HOX treatment was detrimental in general. Apparently, the level of contact with oxygen exhibited a predominant effect on hydroxycinammates and aromas, while the level of grape skin disruption affected primarily hydroxybenzoic acids and flavan‐3‐ols. Practical applications: This study has demonstrated that by choosing grape processing techniques which are different from respect to degree of skin cell disruption and contact with juice, as well as contact with oxygen, it is possible to obtain a variety of white wine styles differing in the content and composition of phenols and volatile aromas, which significantly reflect on their sensory quality. This could be of particular interest for grape varieties with deficient or excessive phenol and aroma potentials, which have to be specifically processed to achieve a satisfactory balance within a desired wine style. Besides deepening the existing and providing new knowledge on the broad topic of grape processing in winemaking, the results obtained are characterized by high level of transferability to wine industry. They may serve experts and producers to draw more precise conclusions on the relative effectiveness of different grape processing techniques, and choose adequate options for their specific needs.